Effects of self-efficacy on relationships between job stressors and job stress among academics at a Research University - Mohammed Shaed, Maslina (2012)
The main purpose of the study is to examine the effects of task-specific self efficacy on the relationship between job stressors and job stress of academics. The study is a quantitative study with correlational research design. The questionnaire used in this study comprised of four sections (respondents’background, job stress, job stressor, and task-specific self-efficacy). The respondents were selected using a stratified random sampling technique and ‘drop and pick’ method was used for data collection. Out of 160 respondents, 128 respondents completed and returned the questionnaires. Data were analyzed using Pearson product-moment correlation, T-test and hierarchical multiple regression to test the relationships, differences and moderation effects. The results of the study revealed that majority of the respondents showed a moderate level of job stress. In contrast, a majority of them showed a high level of workload and under utilization skills and high level of task-specific self efficacy. The analysis of the study indicated that there is a significant difference in job stress based on gender. The correlation analysis showed that role ambiguity, under utilization skills, role conflict, and workload have a positive relationship with job stress. The results of the present study revealed that the predicted moderator of task-specific self-efficacy showed a significant moderation effects on the relationship between job stressors and job stress. Further analysis shows that role conflict and workload have a positive influence in predicting job stress. The study concludes that task-specific self-efficacy have moderating effects on the relationship between job stressors and job stress. It is recommended that the university management should take actions such as provide an appropriate support for academics and training course to reduce the job stressors that caused on job stress among academics staff. It is also recommended that future research should involve large sample and include more variables such as organizational context, family context, personal characteristics and other related variables to measure on job stress among academics staff in Malaysia.